Mathematical Model of a Multiparameter Learning Process - Jurakulov Tolib Tokhirovich (Genius Journals, 2022)
The issues of modeling the learning process as a control object with two or more parameters are considered. The multi-parameter model of the learning process is described in the form of ordinary differential equations. The results of computational experiments are illustrated in the form of graphs.
Keywords: learning process; computer model; mathematical model; differential equation